A boatload of wild Irishmen - Brian Winston; Chris Hainstock; Mac Dara O Curraidhin (2014)
Reissued with three additipnal featuresThe Cinema of Robert FlahertyA 90 minute documentary about the life and film work of Robert Flaherty. Edited at University of Lincoln, filmed in HD from locations around the world. SCript written by Prof Brian WInston.Robert Flaherty (1884-1951) was the man credited with being the father of the modern documentary film after he produced and directed Nanook of the North in 1922. Flaherty is one of the great name directors in the history of cinema and to this day films such as Nanook of the North, Moana, Man of Aran and Louisiana Story are widely regarded as classics and still regularly screened.But this entertaining portrait of Flaherty shrewdly looks beyond standard polemical positions to present a complex view of the man and his work (shown in vivid excerpts). A BOATLOAD OF WILD IRISHMEN includes testimony from Flaherty himself as well as contributions from amongst others, Richard Leacock - cameraman on Louisiana Story (1948) and father of the contemporary hand-held documentary style, Martha Flaherty - Flaherty's Inuit granddaughter, George Stoney - documentary filmmaker and professor at New York University, Seán Crosson - film scholar at the Huston School of Film, Jay Ruby - anthropologist and film scholar at Temple University, and Deirdre NÃ Chonghaile - musician and folklorist from Ãrainn, as well as telling interviews with the people whose parents and grandparents Flaherty put onto the cinema screens of the world: Inuit, Samoans and, of obvious personal interest to the Irish filmmakers, the 'wild men' of Aran.